The Relationship Between Inseminator Characteristics and Ai Result on Livestock in Tabanan Regency - N., Arianti; Inggriati, N. W. T.; Sarini, N. P. (Jurnal Peternakan Tropika; Vol 8 No 1 (2020): Issue 8 No. 1 (2020); January - AprilDO - 10.24843/ejpt.2020.v08.i01.p01, 2020)
The application of artificial insemination technology for increasing livestock population was wellknown throughout the Tabanan regency. However, it was reported that the livestock population in this regency was decreasing recently. The purpose of this study was to find out: 1) inseminator characteristics;  2) inseminator knowledge and skills on artificial insemination (AI); 3) analyzed the relationship between characteristics, knowledge and skills of inseminator to the AI result of the livestock. This research was conducted in Tabanan Regency using 33 respondents who were taken through census method. Primary and secondary data were used in this study the first data was obtained from direct interviews and observations, while secondary data from literature studies. The analysis used was descriptive analysis and Spearman level correlation test. The results showed that: 1) The average age of inseminator, education, workexperience, the number of cows inseminated, were age 51, 12, 16, 13 respectively; 2) inseminator knowledge about artificial insemination was high and inseminator skill was very good; 3) The result of artificial insemination in livestock in Tabanan Regency was categorized good, characteristic factors such as formal education and work experience are positively related to the result of artificial insiminator. While age, number of animals inseminated monthly, knowledge and skills were positively related to the result of artificial insemination in livestock in Tabanan Regency.   Keywords : Inseminator, Artificial Insemination, Result